2012
DOI: 10.1097/ccm.0b013e3182329617
|View full text |Cite
|
Sign up to set email alerts
|

Acute lung injury in critical neurological illness*

Abstract: Acute lung injury/acute respiratory distress syndrome occurred in more than one third of mechanically ventilated neurosciences critical care unit patients. Loss of the cough or gag reflex is strongly predictive of acute lung injury/acute respiratory distress syndrome, while neurologic diagnosis and Glasgow Coma Scale are not. Lower brainstem dysfunction, a clinical marker of neurologic injury not captured by the Glasgow Coma Scale, is a risk factor for acute lung injury/acute respiratory distress syndrome and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 7 publications
1
29
0
1
Order By: Relevance
“…This is similar to the rate of 20–25% observed in studies of ARDS development after subarachnoid hemorrhage and TBI (4, 1012), and 35% reported in a mixed cohort of neurologically ill patients (30). Importantly, this rate is also comparable with that observed in other conditions traditionally viewed as “high risk” for developing lung injury, including sepsis, trauma, and aspiration (31).…”
Section: Discussionsupporting
confidence: 88%
“…This is similar to the rate of 20–25% observed in studies of ARDS development after subarachnoid hemorrhage and TBI (4, 1012), and 35% reported in a mixed cohort of neurologically ill patients (30). Importantly, this rate is also comparable with that observed in other conditions traditionally viewed as “high risk” for developing lung injury, including sepsis, trauma, and aspiration (31).…”
Section: Discussionsupporting
confidence: 88%
“…Reduced mechanical ventilation in the survival group might indicate that disease severity was relatively mild. In addition, decreased mechanical ventilation might result in fewer complications, such as airway injury, infection (especially ventilator‐associated pneumonia), acute respiratory distress syndrome (ARDS), decreased cardiac output, and oxygen toxicity . This might partially explain the higher survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…We appreciate the careful analysis and comments by Dr. Meyer et al (1) regarding our recent publication (2).…”
Section: The Authors Replymentioning
confidence: 91%